Principles of Islamic Religious Education Curriculum Development - Norlianti, Nuni; Aliyah, Siti Rabiatul; Zainuri, Habib (Seutia Hukamaa Cendekia, 2024)
This journal examines the fundamental principles that guide the development of Islamic Religious Education curricula. It highlights the importance of integrating core educational principles such as relevance, efficiency, effectiveness, flexibility, and sustainability, which are essential for creating a curriculum that addresses intellectual achievement and fosters moral and ethical character development in students. The study emphasizes the significance of theological values, primarily derived from the Qur'an and Sunnah, as the foundation for constructing an Islamic Religious Education curriculum that aligns with Islamic teachings. Additionally, the journal explores various philosophical foundations, including essentialism, perennialism, existentialism, and progressivism, that contribute to a diverse approach to the educational process, catering to students' individual needs. In response to the challenges of modern times, it stresses the necessity of adapting the curriculum to the advancements in science and technology while maintaining its religious essence. Ultimately, the research argues for the continuous development and application of a curriculum that integrates relevant educational theories and philosophies, ensuring a well-rounded generation that intellectually and morally excels. The findings suggest that the successful implementation of these principles will result in an effective and sustainable Islamic Religious Education curriculum that can meet the evolving needs of students while fostering strong religious values and ethical conduct